The Republic of Kazakhstan : Financial System Stability Assessment. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Financial System Stability Assessment highlights that the global financial crisis exposed serious bank vulnerabilities in Kazakhstan. The authorities successfully contained the ensuing systemic crisis, however, left unaddressed important weaknesses that continue to linger. The government has nationalized three of the largest banks and restructured their external obligations, thus preventing a collapse of the banking system. The banks' solvency situation is adequate but somewhat fragile as a result of legacy problems. A faster transition to risk-based oversight is needed. The relative vulnerability of banks to shocks warrants increased emphasis on risk. This can be achieved through the adoption of more advanced risk-assessment tools and a more extensive use of stress test results for risk analysis. The financial safety net and resolution framework were upgraded during the crisis but need further adjustments. The government amended the resolution framework in 2009 to incorporate several desirable features such as restructuring, purchase and assumption, and bridge bank. However, during the crisis it bypassed the use of sequential crisis management tools and nationalized banks and restructured their external liabilities. The resolution framework suffers from the absence of special authority and requires the approval of depositors and creditors. Adjustments to the Emergency Liquidity Assistance framework are needed to limit its availability to solvent institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet